Multiparametric MRI as a Noninvasive Monitoring Tool for Children With Autoimmune Hepatitis. Issue 1 (January 2021) - Janowski, Kamil; Shumbayawonda, Elizabeth; Dennis, Andrea; Kelly, Matt; Bachtiar, Velicia; DeBrota, David; Langford, Caitlin; Thomaides-Brears, Helena; Pronicki, Maciej; Grajkowska, Wieslawa; Wozniak, Malgorzata; Pawliszak, Piotr; et al.
ABSTRACT: Objectives: Autoimmune hepatitis (AIH) is a progressive liver disease managed with corticosteroids and immunosuppression and monitored using a combination of liver biochemistry and histology. However, liver biopsy is invasive with risk of pain and bleeding. The aim of the present study was to investigate the utility of noninvasive imaging with multiparametric magnetic resonance imaging (MRI) (mpMRI) to provide clinically useful information on the presence and extent of hepatic inflammation, potentially guiding immunosuppression. Methods: Eighty-one participants (aged 6–18), 21 healthy and 60 AIH patients, underwent multiparametric MRI to measure fibro-inflammation with iron-corrected T1 (cT1) at the Children's Memorial Health Institute in Warsaw alongside other clinical blood tests and liver biopsy at recruitment and after an average of 16-month follow-up (range 9–22 months). Correlation analyses were used to investigate the associations between cT1 with blood serum markers and histological scores. Results: At recruitment, patients with AIH had a higher cT1 value than healthy controls ( P < 0.01). cT1 correlated significantly with key histopathological features of disease. Treatment naïve AIH patients showed evidence of inflammation and heterogeneity across the liver compared to healthy controls. At follow-up, cT1 showed utility in monitoring disease regression as most patients showed significantly reduced fibro-inflammation with treatment ( P < 0.0001) over the observational period. Six patients had histological fibrosis and clear fibro-inflammation on MR despite biochemical remission (normalized aspartate aminotransferase (AST), alanine aminotransferase (ALT), and immunoglobulin G [IgG]). Conclusions: Multiparametric MRI can measure disease burden in pediatric AIH and can show changes over time in response to therapy. Active disease can be seen even in biochemical remission in children.